Src family kinases are required for WNT5 signaling through the Derailed/RYK receptor in the Drosophila embryonic central nervous system. - Wouda, R.R.; Bansraj, M.R.K.S.; de Jong, A.W.M.; Noordermeer, J.N.; Fradkin, L.G. (Development, 2008)
Members of the RYK/Derailed family have recently been shown to regulate axon guidance in both Drosophila and mammals by acting as Wnt receptors. Little is known about how the kinase activity-deficient RYKs transduce Wnt signals. Here, we show that the non-receptor Src family tyrosine kinases, SRC64B and SRC42A, are involved in WNT5-mediated signaling through Derailed in the Drosophila embryonic central nervous system. Analysis of animals lacking SRC64B and SRC42A reveals defects in commissure formation similar to those observed in Wnt5 and derailed mutants. Reductions in SRC64B expression levels suppress a Wnt5/derailed-dependent dominant gain-of-function phenotype, and increased levels of either SRC64B or SRC42A enhance Wnt5/derailed-mediated axon commissure switching. Derailed and SRC64B form a complex, which contains catalytically active SRC64B, the formation or stability of which requires SRC64B kinase activity. Furthermore, Derailed is phosphorylated in a SRC64B-dependent manner and coexpression of Derailed and SRC64B results in the activation of SRC64B. The mammalian orthologs of Derailed and SRC64B also form complexes, suggesting that Src roles in RYK signaling are conserved. Finally, we show that coexpression of WNT5 and Derailed has no apparent effect upon TCF/LEF-dependent transcription, suggesting that the WNT5/Derailed signaling pathway is unlikely to directly regulate canonical Wnt pathway targets. Together, these findings indicate that the Src family kinases play novel roles in WNT5/Derailed-mediated signaling.